Efek Perendaman Benih dengan Pupuk Hayati terhadap Pertumbuhan Bibit dan Serangan Penyakit Rebah Semai pada Tomat (Solanum lycopersicum) - Cendy Monica Wohel; A. Marthin Kalay; Abraham Talahaturuson (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2022)
The use of biofertilizers is part of an environmentally friendly plant cultivation. In order to analyze the effect of soaking seeds with several types of biofertilizers on seedling growth and damping off disease in tomatoes, a greenhouse experiment has been carried out using biofertilizers and the fungicide Propineb as control treatment. The biofertilizers used were mixed biofertilizer (BION-UP), Consortium isolates of tomato rhizosphere bacteria (CITRB), consortium of Azotobacter chrococcum and Trichoderma harzianum (Azoto-Tricho). The results showed that soaking tomato seeds in bioagens solution increased plant height, number of petioles, fresh weight and dry weight of plants, as well as suppressed damping off disease in tomato nursery. The CITRB biofertilizer has a better effect on plant growth and diseases suppression than another biofertilizers and Propineb fungicide. CITRB enable to increase plant height by 49.97%, number of petioles by 60.00%, plant fresh weight by 107.23%, dry weight of plants by 129.41%, and suppress damping off disease by 56.67%. BION-UP, CITRB and Azoto-Tricho were able to suppress damping off disease by 22.22%, 27.78% and 16.67% respectively. The ability of all biofertilizer to suppress damping off disease incidence were better than Propineb fungicide.